Serving Three Masters: The Cultural Gatekeeper's Dilemma. - De Roeper, Julia (Journal of Arts Management, Law & Society)
The author studies the role of cultural gatekeepers in presenting art to the public and the triple responsibilities they bear: to the artist, audience, and investors. How can these three often competing interests be balanced? Conclusions are drawn from interviews with ten Australian cultural gatekeepers working in the performing arts who discussed their programming priorities; these comments are contextualized by statements from eight Australian artists working in various media about the impetus behind their work. The findings of both aspects of the research are considered here for their programming and funding policy implications.